If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c = cx + n Solving c = cx + n Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1cx' to each side of the equation. c + -1cx = cx + -1cx + n Combine like terms: cx + -1cx = 0 c + -1cx = 0 + n c + -1cx = n Combine like terms: n + -1n = 0 c + -1cx + -1n = 0 The solution to this equation could not be determined.
| X^9/x^2 | | 2xy+6a=8x | | v^2+6-7=0 | | 19n=190 | | 3=2w-1 | | 7=v-8 | | -4k+2(5k-6)=-3k-38 | | 1/2(2)-3=y | | 2/3×9/20 | | -7v=140 | | D+30=9 | | C+24=-10 | | (8y-5w)= | | A-8=-14 | | 3q+1=7 | | (X^2+15-8x)=0 | | 5/11b=15 | | 8(x+1)=2(3x+5) | | H/5-19=2 | | 11(b-875)=517 | | x^3+3x^2=13x+9 | | 6log(x-3)=11 | | x+(x+1)-(x+2)+(x+3)= | | 0=v^2-10v+24 | | 6(x-4)=-3(x-4) | | A/9=123 | | f=-2+4x-1+-1x | | 6z^2=-19z-10 | | H--184/22=30 | | x^2+y^2+16x+12y=0 | | 22/h--184=30 | | S/3=4 |